CHEMICAL CONSTITUENTS AND ANTIOXIDANT PERSPECTIVES OF EXTRACTS OF CHARA GLOBULARIS AND CLADOPHORA SPECIES (STRING ALGAE) SPECIES - M, Karpakavalli; Ay, Sangilimuthu; S, Mohan (Asian Journal of Pharmaceutical and Clinical Research, 2018)
Objectives: Marine organisms are capable of producing unusual bioactive compounds that are not observed in terrestrial sources. Algae are now drawing a greater interest following the increase in demand for biodiversity in the screening programs seeking therapeutic drugs from natural products. Methods: Hot acid extraction and cold alkali extraction of Chara globularis and Cladophora species (string algae), respectively, were carried out successfully. The extracted materials were tested for the qualitative reactions and subjected for thin-layer chromatography, ultraviolet, and infrared spectral studies so as to characterize the extracted materials of two algae. They were estimated for their antioxidant perspectives by hydrogen peroxide radical scavenging and reducing power assay methods. Results: Percentage yield of the extracts was found to be 80% and 40%, respectively, for the two algal species. The IC50 value of hydrogen peroxide scavenging activity of C. globularis and Cladophora species was found to be 30 Î¼g/ml and 20 Î¼g/ml, respectively, and the same for the standard ascorbic acid was 20 Î¼g/ml. The results were found to be dose dependent, i.e., higher the concentration, and more was the scavenging activity. Conclusion: Despite the widespread uses and claimed advantages of the algae, only a few investigations on the chemical composition have been reported. A good correlation between the structure and activities of these most popular categories can be brought about.